Strategies to Conquer The Souvenir Business: Case Study of lapis Talas Cake Bogor - Ahmad Ridho; Idqan Fahmi; Siti Jahroh (Indonesian Journal of Business and Entrepreneurship (IJBE), 2019)
The objectives of this study are 1) to analyze the effect of marketing mix, brand awareness, brand image and region of origin on lapis talas purchasing decision for tourists in Bogor city, 2) to create effective marketing strategies for business development. Using SEM-Partial Least Square method,this research was conducted in the city of Bogor with the sample of 160 respondents. The selected respondents were tourists who came to the city of Bogor and had purchased lapis talas cakes. From the results of the study, it is known that the brand awareness variable, brand image, product, promotion and region of origin have a significant influence while the place variable has no significant influence. Strategy recommendations suggested in this study are 1) Increase brand awareness by increasing the intensity of advertising on social media, building outlets in tourism areas and train stations; 2) Improve product quality by providing packaging machines, making plastic bags, enlarging product sizes and adding fruit mixes; 3) Improve regional characteristics by adding taro ingredients and making a brand that is identical with the city of Bogor; 4) Build brand image through tagline; 5) Increase promotion using online media (facebook, instagram and twitter), billboards and discounted prices.Keywords: marketing mix, marketing strategy, region of origin, SEM-PLS, purchase decision